3δ principle and boxplot method are used to estimate the cost interval of tower replacement technology. (June 2020) - Li, Jianqing; Zhu, Xiaohu; Zhao, Chen; Kang, Jian
Abstract: The replacement of tower is an important part of the technical reform of power grid lines. To analyze the rationality of the cost of the technical reform of tower, it is necessary to deal with the abnormal engineering data based on the cost data of previous projects. In this paper, the unit cost of tower replacement is sorted out by using 3δ principle and boxplot method, and the reasonable cost range is obtained to provide a basis for project investment.